PERAN GURU SEBAGAI KONSELOR ISLAMI DALAM PELAKSANAAN BIMBINGAN THE SELF SISWA DI SMP MUHAMMADIYAH SATU TELUK KUANTAN - Ladira Wala Dirara (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Counselors according to Islamic teachings are people who help or guide someone, a group of people who are facing a problem with the aim of fixing it to achieve the safety of the world and the hereafter. Guidance and assistance is carried out by providing a variety of knowledge, attitudes, and skills so that the counselee is able to get solutions about the problems he faces.The objectives in this study 1. How is the Role of Teachers as Islamic Counselors in the Implementation of the Self-Student Guidance in SMP Muhammadiyah Satu Teluk Kuantan. 2. Factors affecting the Role of Teachers as Islamic Counselors in the Implementation of the Self-Student Guidance at SMP Muhammadiyah Satu Teluk Kuantan.Based on the analysis of the author's research data the Role of the Teacher as an Islamic Counselor in the Implementation of the Self Student Guidance at SMP Muhammadiyah Satu Teluk Kuantan, is categorized as "Good" in the range of 76% - 100% which is 93.7%. Then the factors that influence the Role of Teachers as Islamic Counselors in the Implementation of the Self Student Guidance in SMP Muhammadiyah Satu Teluk Kuantan, namely 1. Environmental Factors 2. Initiative Factors. 3. Room Setting Factors.